Feasibility and effectiveness of hysteroscopic myomectomy for type 3 myomas - Yan, Hui; Li, Junwei; Wang, Tingting; Liu, Zhong (Frontiers in Surgery, 2026)
ObjectiveThis study aimed to evaluate the feasibility and effectiveness of hysteroscopic myomectomy for treating International Federation of Gynecology and Obstetrics type 3 myomas.MethodsThis retrospective study evaluated 26 patients with type 3 myoma who underwent hysteroscopic myomectomy in a teaching hospital between January 2022 and May 2025. Data on surgery time, transurethral resection of prostate syndrome, and complete removal rate were collected. The amount of menstruation which was assessed by pictorial blood loss assessment chart (PBAC). The PBAC, duration of menstrual period, and hemoglobin levels were recorded at 3, 6, and 12 months postoperatively.ResultsThe complete myoma removal rate was 96.15%. One patient developed transurethral resection of prostate syndrome, while no cases of postoperative intrauterine adhesion were detected on three-dimensional (3D) transvaginal ultrasound. A significant reduction in menstrual blood loss was observed after the procedure. Notably, three women conceived naturally within 1 year postoperatively.ConclusionHysteroscopic myomectomy is a viable treatment option for International Federation of Gynecology and Obstetrics type 3 myomas and can effectively relieve menorrhagia in highly selected patient population.